1982
DOI: 10.1111/j.0954-6820.1982.tb01928.x
|View full text |Cite
|
Sign up to set email alerts
|

Urine Microscopy as Screening Method for Bacteriuria

Abstract: ABSTRACT. Fresh urine samples from 90 ambulatory patients with urological disorders were examined for leucocytes by counting the number of WBC/mm3 and per high power field (HPF) in sediment. Bacteria could be cultured in 20 samples, 18 of which contained >8 WBC/mm3. Two (3%) of the 63 samples with ±8 WBC/mm3 contained bacteria. Bacteriuria was found in two (3%) of 65 samples containing 0–1 WBC/HPF. Microscopic examination of the sediment might be used for the screening of patients with a high frequency and ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It was noted in our study that among women with uncomplicated UTI, a 5-day course of nitrofurantoin showed a better clinical and microbiological resolution than compared to single dose fosfomycin (3)(4)(5) when observed at 28 days of therapy completion.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It was noted in our study that among women with uncomplicated UTI, a 5-day course of nitrofurantoin showed a better clinical and microbiological resolution than compared to single dose fosfomycin (3)(4)(5) when observed at 28 days of therapy completion.…”
Section: Discussionmentioning
confidence: 56%
“…Antimicrobial resistance is increasing at an alarming rate and mandates the need for microbiological testing before starting antibiotics. Individualising patient management, reviewing and conducting surveillance on existing guidelines, judicious use of existing antibiotics, development of new antimicrobial agents and strict infection control practices pave way to reduce the spread of (3,4,6,7) resistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiological methods are used to specify bacteria and fungi from sampled body fluids and blood as well as to test their susceptibility to antibiotic agents. Microscopy and Gram staining are simple and rapid techniques to identify bacteria and fungi in the sputum, urine, cerebrospinal fluid, ascites, and other body secretions [43][44][45][46][47][48][49]. The appearance and staining of bacteria can categorize (Gram positive/negative) and identify selected bacterial species (e.g., meningococci, pneumococci, staphylococci), thus allowing for prompt adjustment of empiric antibiotic therapy.…”
Section: Identification Of the Causative Microbiological Pathogenmentioning
confidence: 99%